(untitled) (Eurasian Scientific Herald, 2023)
Information technology plays a critical role in diabetes management by providing tools to monitor blood sugar levels, manage insulin therapy, provide remote counseling, and offer educational resources. These advances help people with diabetes better understand and manage their condition, leading to improved health.